PENERAPAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 003 TEMBILAHAN KOTA KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Rahimah Rahimah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low learning outcomes of mathematics students, from 20 students only 7 students (35%) with an average value of 56.00. This study aims to improve students' mathematics learning outcomes by applying the image media in the learning process. This research is a classroom action research, conducted in class IV SDN 003 Tembilahan Kota, this research is conducted in two cycles with four stages: planning, implementation, observation and reflection. The result of research indicate that the acquisition of mathematics learning outcomes of students in cycle I the total number of students who completed totaled 13 students (65.00%) with an average score of 72.50. In cycle II the number of completed students amounted to 19 students (95.00%) with an average score of 83.25. Based on the results of this study, it can be concluded that the application of image media can improve student learning outcomes of grade IV SDN 003 Tembilahan Kota, Kecamatan Tembilahan, Kabupaten Indragiri Hilir.